The limits of underpotential deposition in the nanoscale - Oviedo, Oscar Alejandro (2012)
A thermodynamic model predicting the disappearance of the underpotential deposition phenomenon in the limit of small nanoparticles is proposed and developed for selected families of geometric bodies. The key parameters are the binding energy of adatoms on the flat foreign substrate and at the edges of the nanoparticle. © 2012 Elsevier B.V. All rights reserved.